The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/bi00194a021
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Dependent ATPase from HeLa Cells Is Related to Human Ku Autoantigen

Abstract: A 150-kDa DNA-dependent ATPase composed of 83/68-kDa subunits was previously reported to cofractionate with a 21S complex of enzymes for DNA synthesis from HeLa cells (Vishwanatha, J. K., & Baril, E. F. (1990) Biochemistry 29, 8753-8759). The DNA-dependent ATPase was purified to electrophoretic homogeneity from a HeLa cell homogenate by a modified procedure that involves subcellular fractionation, poly(ethylene-glycol) precipitation of the combined nuclear extract/cytosol, and chromatography on Q-Sepharose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 51 publications
0
52
0
Order By: Relevance
“…The tight association of these enzymatic activities with DNA are reminiscent of a DNA-dependent protein kinase/ATPase complex detected in HeLa cells (15)(16)(17)(18). The latter complex has been suggested to be involved in the regulation of transcription, DNA replication and cell growth (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tight association of these enzymatic activities with DNA are reminiscent of a DNA-dependent protein kinase/ATPase complex detected in HeLa cells (15)(16)(17)(18). The latter complex has been suggested to be involved in the regulation of transcription, DNA replication and cell growth (17).…”
Section: Discussionmentioning
confidence: 99%
“…The latter complex has been suggested to be involved in the regulation of transcription, DNA replication and cell growth (17). Although the physical constants ofthe previously described complex are clearly different (16)(17)(18), it is of interest that a combined protein kinase/ATPase activity has been correlated with DNA transcription and replication (17), functions that are also expected to be associated with the bases of DNA loops (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical analyses of Ku demonstrated that it bound in vitro to DNA termini or other discontinuities in the DNA structure without apparent sequence speciÂźcity (Minori and Hardin, 1986;Blier et al, 1993;Falzon et al, 1993). Ku has also been shown to possess DNA-dependent ATPase (Cao et al, 1994) and helicase (Tuteja et al, 1994) activities. Lastly, Ku has also been reported to be capable of sequence-speciÂźc binding within the promoter elements of genes (Gri n et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…22 Biochemical analyses of Ku demonstrated that it bound in vitro to DNA termini in the DNA structure without apparent sequence specificity. [23][24][25] Ku has also been shown to possess DNA-dependent adenosine triphosphatase 26 and helicase 27 activities. In vitro, heterodimerization of active Ku requires the cotranslation of both subunits.…”
mentioning
confidence: 99%